5-Lipoxygenase-Activating Protein as a Modulator of Olanzapine-Induced Lipid Accumulation in Adipocyte. (25th May 2013) - Dzitoyeva, Svetlana; Chen, Hu; Manev, Hari
Abstract : Experiments were performed in 3T3-L1 preadipocytes differentiated in vitro into adipocytes. Cells were treated with olanzapine and a 5-lipoxygenase (5-LOX) activating protein (FLAP) inhibitor MK-886. Lipid content was measured using an Oil Red O assay; 5-LOX and FLAP mRNA content was measured using quantitative real-time PCR; the corresponding protein contents were measured using quantitative Western blot assay. Olanzapine did not affect the cell content of 5-LOX mRNA and protein; it decreased FLAP mRNA and protein content at day five but not 24 hours after olanzapine addition. In the absence of MK-886, low concentrations of olanzapine increased lipid content only slightly, whereas a 56% increase was induced by 50 μ M olanzapine. A 5-day cotreatment with 10 μ M MK-886 potentiated the lipid increasing action of low concentrations of olanzapine. In contrast, in the presence of 50 μ M olanzapine nanomolar and low micromolar concentrations of MK-886 reduced lipid content. These data suggest that FLAP system in adipocytes is affected by olanzapine and that it may modify how these cells respond to the second-generation antipsychotic drugs (SGADs). Clinical studies could evaluate whether the FLAP/5-LOX system could play a role in setting a variable individual susceptibility to the metabolic side effects of SGADs.